Antisense oligonucleotide treatment produces a type I interferon response that protects against diet-induced obesity - Kristin M. McCabe; Joanne Hsieh; David G. Thomas; Matthew M. Molusky; Liana Tascau; Jun B. Feranil; Li Qiang; Anthony W. Ferrante, Jr.; Alan R. Tall (Molecular Metabolism, 2020)
Objective: In mouse models, deficiency of TTC39B (T39) decreases hepatic lipogenic gene expression and protects against diet-induced steatohepatitis. While assessing the therapeutic potential of antisense oligonucleotides (ASOs) targeting T39, we discovered an unexpected weight loss phenotype. The objective of this study was to determine the mechanism of the resistance to diet-induced obesity. Methods: To assess therapeutic potential, we used antisense oligonucleotides (ASO) to knock down T39 expression in a Western or high-fat, high-cholesterol, high-sucrose-diet-fed Ldlr−/− or wild-type mice. Results: T39 ASO treatment led to decreased hepatic lipogenic gene expression and decreased hepatic triglycerides. Unexpectedly, T39 ASO treatment protected against diet-induced obesity. The reduced weight gain was seen with two different ASOs that decreased T39 mRNA in adipose tissue macrophages (ATMs), but not with a liver-targeted GalNac-ASO. Mice treated with the T39 ASO displayed increased browning of gonadal white adipose tissue (gWAT) and evidence of increased lipolysis. However, T39 knockout mice displayed a similar weight loss response when treated with T39 ASO, indicating an off-target effect. RNA-seq analysis of gWAT showed a widespread increase in type I interferon (IFN)-responsive genes, and knockout of the IFN receptor abolished the weight loss phenotype induced by the T39 ASO. Some human T39 ASOs and ASOs with different modifications targeting LDLR also induced a type I IFN response in THP1 macrophages. Conclusion: Our data suggest that extrahepatic targeting of T39 by ASOs in ATMs produced an off-target type 1 IFN response, leading to activation of lipolysis, browning of WAT, and weight loss. While our findings suggest that ASOs may induce off-target type 1 IFN response more commonly than previously thought, they also suggest that therapeutic induction of type 1 IFN selectively in ATMs could potentially represent a novel approach to the treatment of obesity. Keywords: Obesity, White adipose tissue, Type I interferon, Antisense oligonucleotides, Adipose tissue macrophages